(untitled) (Research, Society and Development, 2021)
Pu-erh is a fermented Chinese tea with characteristics of mild, woody flavor and dark red color. The preparation of the tea starts from leaves of Camellia sinensis in natura that undergo a drying in the sun. Its classification is given in two categories: a raw tea similar to green tea and a matured tea that is fermented. Matured tea has a higher market value due to the processes involved in manufacturing, especially in terms of aging. Pu-erh has numerous benefits for human health, which are closely related to the bioactive profile of the main chemical components of tea, being polyphenols, theabrownins, flavonols, polysaccharides, amino acids and alkaloids. The increasing introduction of Pu-erh tea in the diet of consumers results in the need to explore information associated with consumption through analysis of the available literature, addressing current scientific evidence. Therefore, the present review sought to elucidate the fermentative process of Pu-erh tea production, its chemical composition, its sensory aspects and health benefits.